Regulating addictive algorithms and designs: protecting older adults from digital exploitation beyond a youth-centric approach - Yao, Yu (Frontiers in Psychology, 2025)
As digital technologies evolve, addictive algorithms and designs (aADs) have become a significant public health concern, particularly for older adults, a demographic often overlooked in digital addiction (DA) discourse. Compared to younger users, some older adults may face increased susceptibility to aADs due to factors such as cognitive changes, social isolation, physical comorbidities, or limited digital literacy. These designs, which exploit features like infinite scrolling, are associated with higher risk of compulsive use and may correlate with long-term impacts on cognitive health, social functioning, and quality of life for certain subgroups of older adults. Existing regulatory frameworks predominantly focus on protecting minors, often neglecting the distinct needs and vulnerabilities within aging populations. This paper advances a pluralistic governance framework that recognizes the diversity among older adults. Recommended measures include behaviorally informed disclosures, algorithmic transparency, tailored digital literacy programs, culturally responsive safeguards, and antitrust actions against exploitative design. Age-inclusive regulation is urgently needed to address potential risks of digital dependency, mental health concerns, and social inequalities among aging populations. Addressing these challenges requires collaboration across sectors to ensure digital environments support autonomy and well-being at all ages.